Prevalence of vitamin B 12 deficiency and associated factors among primary school children: North East Ethiopia: multicenter cross-sectional study - Ermiyas Endewunet Melaku; Besufekad Mulugeta Urgie; Alemnesh Tesema Tilahun; Hilina Ketema Assefa; Alemayehu Abera Abebe; Aklile Semu Tefera (BMC, 2024)
Abstract Background The prevalence of Vitamin B12 deficiency is common and is more frequent in low- and middle-income countries with a poor or inadequate diet of animal foods. In Ethiopia, researches related to the status of micronutrients in children are limited. Therefore, this study aimed to assess the prevalence of vitamin B12 deficiency and associated factors among primary school children. Methods A cross-sectional study design was conducted from January 10-February 30/2023. A total of 514 students were selected using a systematic random sampling technique. Face-to-face interviews using a structured questionnaire, document review, anthropometric measurement, and laboratory studies were implemented to collect data. Data was analyzed by STATA version 14 and summarized by using frequency tables and graphs. Logistic regression analysis was done to identify factors associated with vitamin B12 Deficiency. Results About 34% of the students were found to have vitamin B12 deficiency. Not Consuming animal products (AOR = 1.83, 95% CI:1.20-2.79) and low body mass index (AOR = 1.62, 95% CI:1.05-2.47) were associated with vitamin B12 deficiency. Conclusions The study revealed a notable high deficiency of vitamin B12 in primary school students. Consumption of animal products and BMI were identified as statically significant associated factors with serum concentration of vitamin B12.